The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00330-017-5259-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion magnetic resonance imaging for differentiating metastatic and non-metastatic lymph nodes in pancreatic ductal adenocarcinoma

Abstract: • IVIM DWI is feasible for diagnosing LN metastasis in PDAC. • Metastatic LNS has lower D, D*, f, ADC values than non-metastatic LNS. • D-value from IVIM model has best diagnostic performance, followed by ADC value. • D* has the lowest AUC value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The aggressive biological behavior of tumors may be associated with the difference in tumor microstructure. Our results suggested that MD of the tumor with LNM had a lower MD value, which is consistent with most previous studies on pancreatic cancer and cholangiocarcinoma [13,24,28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The aggressive biological behavior of tumors may be associated with the difference in tumor microstructure. Our results suggested that MD of the tumor with LNM had a lower MD value, which is consistent with most previous studies on pancreatic cancer and cholangiocarcinoma [13,24,28].…”
Section: Discussionsupporting
confidence: 93%
“…MRI with diffusion-weighted imaging (DWI) can be used to noninvasively assess the pancreatic tumor, neighboring soft tissues, microvascular invasion, water diffusion behavior, and LNM in one examination [11]. Several studies have reported positive results for identifying metastatic lymph nodes in pancreatic tumors through the use of MRI findings, apparent diffusion coefficient (ADC), and intravoxel incoherent motion (IVIM) [11][12][13]. It is possible that MRI with DWI might show differences in morphology, water diffusion, heterogeneity, and microenvironment characteristics among metastatic and non-metastatic for small lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…35 Recent studies using nomograms based on radiographic features of contrastenhanced CT scans demonstrate promising rates of positive lymph node identification in both the test and validation cohorts. 36,37 With similar advances in progress using abdominal MRIs 38 and based on the aforementioned implications of an elevated lymph node positive ratio on early disease recurrence demonstrated in our analysis, improving imaging modalities may facilitate more judicious patient selection for surgery following NAT.…”
Section: Discussionmentioning
confidence: 58%
“…For the pelvic lymph nodes in prostate cancer (including a small group of a bladder cancer patients in one study) from 910 to 1430 × 10 -6 mm 2 /s [27,[39][40][41]. For the abdominal lymph nodes in biliary carcinomas 1800 × 10 -6 mm 2 /s 37 or in pancreatic ductal adenocarcinoma 1390 × 10 -6 mm 2 /s [38]. For the axillary lymph nodes in breast cancer from 812 to 1300 × 10 -6 mm 2 /s [26,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%